KOMUNIKASI ANTARBUDAYA MAHASISWA ASING DENGAN MAHASISWA PRIBUMI (Studi Kualitatif dengan Pendekatan Interaksi Simbolik Pada Interaksi Mahasiswa Asal Malaysia, Thailand, Vietnam dengan Mahasiswa Pribumi di UIN SUSKA Riau) - Ramos Roshima; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Being foreign student at university require person to adapted with new culture and interact with native student who have different culture background. The cross culture communication happened between foreign student from Malaysia, Thailand, also Vietnam with native student in UIN SUSKA Riau campuses that include adaptive and accommodative communication behavior. On accommodate other culture process foreign student did accommodation strategies involved such as doing convergence, divergence, and overaccomodation. This study aims to determine the intercultural communication behavior of foreign students with native students and communication barriers faced by foreign students while in UIN SUSKA Riau.This study used qualitative methods with symbolic interactionism approach. The research located at Sultan Syarif Kasim Islamic State University in Pekanbaru, Riau Province. This study took nine informants and determined by using purposive technique. Types and sources of data obtained through the primary data and secondary data. Data collection is done with depth interviewed, observation in research location, and completed with documentation along the research. The data processing by using Huberman and Miles interactive data analysis technique with an examination of thedata validity through the extension of participation and triangulation.This study result show that in intercultural interactions the foreign students showed accommodative behavior like convergence in verbal and nonverbal form when adapting also divergences in communication accommodation which made by foreign students with native students. Foreign students also experienced excessive accommodation from native students when adapting. Intercultural Communication between foreign students and natives students also experienced barriers such as cultural barriers, linguistic, differences in perception and nonverbal habits differencial.Keywords: cross culture communication, accomodation strategies, UIN SUSKA Riau